The Representation of Roma in the Romanian Media During COVID-19: Performing Control Through Discursive-Performative Repertoires - Chiruta, Ionut (Frontiers in Political Science, 2021)
Blaming ethnic and disadvantaged groups for spreading COVID-19 was one of the myriad phenomena propelled during the pandemic. Romania, the country with the highest number of Roma people in Eastern Europe, i.e., 1.8 million people, witnessed an increase in chauvinism during the first national lockdown. Aroused by the influx of ethnic Romani returning from Western Europe, the Romanian mainstream media expanded its coverage, revitalizing the majority’s stereotypes. Confrontations between the police and some Romani communities triggered nationwide reporting through sensationalist headlines. Labeled as not complacent with the rules drafted by national authorities, the Roma were beleaguered by the press and police. Hence, this present study asks how the language employed by the media to describe the events revolving around Roma communities underwent discursive-performative practices of control during COVID-19? This study adopts as its case study the town of Țăndărei. The latter is a small town from the south of Romania, predominantly inhabited by ethnic Romani, which was under quarantine between April-May 2020. Two types of data will help investigate the main research question of this study. Firstly, this paper uses the government's military ordinances (e.g., normative acts that instituted lockdown). Secondly, this paper uses primary data from the main Romanian broadcasters (5) and the main written press (6). Herein, the paper tries to assert the links between the government response and media coverage to identify the elements that led to the transformation of the discursive landscape. To do so, this article analyzes via discourse analysis using the NVivo software the headlines of approximately 291 articles that covered between February-June the development of COVID-19 in Romania. Findings from the study indicate that media underwent a gradual discursive process relying on hyperboles, stereotypes, and outlining the antagonism between the Roma and the police.